A rare complication of COVID-19 infection: bilateral spontaneous pneumothorax and pneumomediastinum - Can, Atilla; Yıldıran, Hüseyin; Ergün, Recai; Tülek, Baykal (Journal of Surgery and Medicine, 2022)
Coronavirus 2019 (COVID-19) infection has affected the whole world since the end of 2019. Patients with the disease may present with various symptoms and develop various associated complications. Spontaneous bilateral pneumothorax and pneumomediastinum can also be detected in patients with COVID-19 who do not receive positive pressure ventilation support and do present with an intense cough. A case of bilateral spontaneous pneumothorax and pneumomediastinum over the course of the COVID-19 infection in a young male patient is reported.